Behavioural Decision Making and Suggestional Processes - Molz, Günter; Justus Liebig University Giessen (My University, 2001)
Common features between the domains of behavioural decision making and suggestional processes are discussed. These features areallocated in two aspects. First, behavioural decision making and suggestional processes are traditionally considered to provokeinadequate human behaviour. In this article arguments are put forward against this interpretation: Actions induced by non-rational decisionsand / or by suggestional processes often have adaptive functions. Second, two common thematic issues are discussed ((1) utility functionsin behavioural decision making, (2) ambiguity avoidance) that could be investigated empirically within an integrated framework ofbehavioural decision making and suggestional processes.
Keywords: Psychology; Rationality; Behavioural decision making; Suggestional processes; Philosophy of decision sciences; ddc:150